Abstracts of the 46th Annual Conference of Young Scientists ‘Cold in Biology and Medicine. Current Issues in Cryobiology, Transplantology and Biotechnology’ May 25, 2022 - Problems of Cryobiology and Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):292–294